Design de moda: a cultura de projeto na moda com base nos conceitos do design estratégico - Nicchelle, Keila Marina (Universidade do Vale do Rio dos Sinos, 2011)
This investigation shows that fashion is becoming to be thought, in the contemporaneous context, in a complex and systemic way, according to the theoretical-methodological principles of design. To reach this dimension, fashion and design more and more approach to each other, both in practice and in theory, constituting a universe of culture of project. Thus, fashion design, as culture of project, may be questioned according to the conjecture of strategic design. This investigation aims at discussing fashion design as a culture of project, based on the concepts which define strategic design for the configuration of a methodology of strategic project applied to fashion design in an industrial context. This approach is justified due to the fact that the construction of a methodology of strategic project applied to fashion design is fundamental as a knowledge platform for project practice in fashion as innovation strategy. In this sense, the adopted methodology for the performance of this investigation consists of a case study, developed by means of interviews with managers and designers of three factories in the field of fashion located in the city of Erechim/RS. The analysis of data obtained through the case study and the crossing of this information with theoretical basis made possible the understanding of the process of fashion design in an industrial context. In the same manner, the relation established among the methods of the project developed in fashion design and in strategic design made possible the identification of theoretical-methodological principles complementary to fashion design process, mainly when considering the limits and contributions of strategic design for fashion design. On its turn, the study allowed to answer the problem of the investigation, that is, what defines fashion design in an industrial context and what the contribution of strategic design for fashion design is. Finally, a methodology of strategic project applied to fashion design is suggested, this way, fulfilling the objectives here proposed.
Keywords: Design de moda; Design estratégico; Cultura de projeto; Fashion design; Strategic design; Culture of project; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial